2017
DOI: 10.7575/aiac.ijels.v.5n.2p.61
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cultural Identity, Intrinsic Motivation and Pronunciation Knowledge of Iranian EFL Learners

Abstract: Gardener’s (1985) socio-cultural model shows that culture is among the variables that can affect learning languages. In addition, a series of studies were prompted by Dörnyie (2005) to gauge the effect of motivation on language learning. This correlational study endeavored to find out any possible interaction between these variables, i.e., cultural identity, intrinsic motivation, and pronunciation knowledge of Iranian EFL learners at intermediate level. To this end, 9 items from Mathews’ Cultural Identity Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Language and culture are fundamental barriers that hinder cross-cultural communication between people [25]. As socio-cultural context plays an important role in determining one's proficiency in English language, the presence of multiple variables such as books, foreign radio, internet, films, and newspaper and magazines contributed to the differences occurred in a language [26]. According to Ahmadi and Bajelani [27], in terms of learning process, English for specific purposes (ESP) has no different from other teaching processes.…”
Section: Language and Culturementioning
confidence: 99%
“…Language and culture are fundamental barriers that hinder cross-cultural communication between people [25]. As socio-cultural context plays an important role in determining one's proficiency in English language, the presence of multiple variables such as books, foreign radio, internet, films, and newspaper and magazines contributed to the differences occurred in a language [26]. According to Ahmadi and Bajelani [27], in terms of learning process, English for specific purposes (ESP) has no different from other teaching processes.…”
Section: Language and Culturementioning
confidence: 99%
“…This finding was also related to Shabani and Alipoor (2017), who found that students with high scores in pronunciation were typical of motivated students. From that point, it can be concluded that someone who has high learning motivation in learning pronunciation will influence their pronunciation during learning or the result of the learning.…”
Section: Problems Faced In Learning Pronunciationmentioning
confidence: 57%
“…IM also contributes to long-term language learning success and autonomy. They are likely to spend more time on learning and perform higher in language proficiency (Shabani, 2017).…”
Section: B Intrinsic Motivationmentioning
confidence: 99%